“Efectos de tres sustratos sobre la capacidad de oviposición de sitotroga cerealella (olivier) para la producción masal de trichogramma pretiosum riley en el distrito de buenos aires-provincia de Picota” - Espiritu Cisterna, Alexander Vince (2004)
The present experiment was carried out on the biological control laboratories from San Femando company. lt is located on Buenos Aires district county of Picota, San Martin Region, among the months of February to June of 2003, in order to finding the best sustrat for our hosted breeding and its influence in eggs production for massive breeding of parasite-like Trichogramma pretiosum, comparing three different sustrats as: soft com, wheat, and sorghum with three levels of Sitotroga cerea/ella egg concentration we use a totally randomized under a Design with factorial arrangement 3 x 3 with three repetitions whose factors were A1 corn, A2 wheat, A3 sorghum, and factor 81 0,5 g of Sitotroga eggs, 82 0,75 g of Sitotroga eggs, A3 1,0 g of Sitotroga eggs, making a total of 9 treatments and three repetitions, the gatherings of posturas of Sitrotroga cerea/ella were evaluated each 2 days until 75 days production analyzing the quality control for each species. After statistical analyses was determinad that sorghum, in all its treatments obtained the biggest production of posturas overcoming to wheat and com, also it was noticed that minimum quantity of little eggs plus sorghum sustrat that is to say A1B3 (0,5 g of Sitotroga little eggs in 15 kg sustrate). They Overcame to rest of repetitions of other sustrats with the biggest concentration of postures, demonstrating that it is definitively an unquestionable effect of sustrat, exists on final Sitotroga cerea/ella eggs yielding, and it is very indispensable for the massive breeding of our parasite-like Trichogramma pretiosum Riley.